PREPARATION AND PROPERTIES OF SHIGA TOXIN AND TOXOID - Dubos, René J. (The Rockefeller University Press, 1946)
1. Shigella dysenteriae (Shiga) can, under the proper cultural conditions, produce a soluble toxin which is independent of the specific somatic polysaccharide antigen. A method is described for the rapid production of this toxin by an avirulent R variant of this organism. 2. The amount of bacterial protoplasm synthesized, and the yield of toxin produced, are very much increased when the culture is grown under conditions which favor aerobic metabolism and which do not permit accumulation of organic acids. 3. Although addition of an excess of inorganic iron to the medium does not interfere with the synthesis of bacterial protoplasm, maximal toxin production is obtained only in media which have been freed of the metal. 4. R Shiga bacilli grown under conditions of extreme aerobiosis at pH 7.0 in a simple medium free of inorganic iron and containing fumaric acid, glucose, meat extract, and peptone, give rise within 24 to 36 hours to cultures exhibiting a high degree of toxicity. The toxic principle rapidly becomes soluble as the cells die; it can be concentrated, purified, and freed of phosphorus by selective precipitation methods. 5. The toxin is fairly resistant to heat at pH 6.0 but rapidly denatured at pH 9.0. It is only slowly inactivated by trypsin. It filters readily and without loss of activity through anionic exchange resins but is precipitated and adsorbed by cationic resins which retain the nitrogen and toxic activity of the preparation. 6. The most active preparations of toxin available possess an LD(50) of 1 to 10 µg. for mice and rabbits. Young mice (up to 5 weeks of age) are more resistant than older animals. 7. The soluble toxin can be detoxified by treatment with 0.5 per cent formalin at pH 8.5; detoxification does not take place at lower pH whereas treatment at higher pH destroys specific antigenicity. Mice immunized with Shiga toxoid (in solution, or in the form of an alum precipitate) develop active immunity to the toxin.